Senescence‐associated superoxide dismutase influences mitochondrial gene expression in budding tunicates. (16th May 2013) - Kawamura, Kaz; Sunanaga, Takeshi
<x xml:space="preserve">Abstract</x> A recent study has shown that in the budding tunicate Polyandrocarpa misakiensis, the mitochondrial respiratory chain (MRC) dramatically attenuates the gene activity during senescence. In this study, we examined the possible involvement of superoxide dismutase (SOD) in the attenuation of gene expression of cytochrome c oxidase subunit 1 (COX1) in aged zooids. By RT‐PCR and in situ hybridization, Cu/Zn‐SOD (SOD1) was found to be expressed in most cells and tissues of buds and juvenile zooids but showed a conspicuous decline in senescent adult zooids, except in the gonad tissue in which the cytoplasm of juvenile oocytes was stained heavily. This expression pattern of SOD1 was similar to that of COX1. In contrast to SOD1, Mn‐SOD (SOD2) was expressed constitutively in both somatic and germline tissues of buds, juvenile zooids, and senescent adult zooids. Knockdown of SOD1 by RNAi diminished the gene activity of not only SOD1 but also of COX1. The resultant zooids had transient deficiencies in growth and budding, and they recovered from these deficiencies approximately 1 month later. Our results indicate that in P. misakiensis, SOD1 is a senescence‐associated nuclear gene and that the experimental decline in SOD1 gene expression accompanies the attenuation of MRC gene activity. Although it is uncertain how SOD1 is downregulated during tunicate senescence, the decreased SOD1 activity could be one of the main causes of MRC gene attenuation during normal senescence.